Safety and immunogenicity of DNA/modified vaccinia virus ankara malaria vaccination in African adults. - Moorthy, V; Pinder, M; Reece, W; Watkins, K; Atabani, S; Hannan, C; Bojang, K; McAdam, K; Schneider, J; Gilbert, S; Hill, A (2003)
The present study is an investigation of the safety and immunogenicity of DNA and modified vaccinia virus Ankara (MVA) candidate vaccines, each encoding the malaria DNA sequence multiple epitope-thrombospondin related adhesion protein (ME-TRAP), against Plasmodium falciparum. DNA ME-TRAP and MVA ME-TRAP are safe and immunogenic for effector and memory T cell induction. MVA ME-TRAP, with or without prior DNA ME-TRAP immunization, was more immunogenic and more cross-reactive in malaria-exposed individuals than in malaria-naive individuals, a finding suggesting that recombinant MVA vaccines are particularly promising for the development of a malaria vaccine for exposed populations. Both CD4(+) and CD8(+) T cells were induced by these vaccines.